Enzyme‐Controlled Nanodevice for Acetylcholine‐Triggered Cargo Delivery Based on Janus Au–Mesoporous Silica Nanoparticles. Issue 18 (15th March 2017) - Llopis‐Lorente, Antoni; Díez, Paula; de la Torre, Cristina; Sánchez, Alfredo; Sancenón, Félix; Aznar, Elena; Marcos, María D.; Martínez‐Ruíz, Paloma; Martínez‐Máñez, Ramón; Villalonga, Reynaldo
Abstract: This work reports a new gated nanodevice for acetylcholine‐triggered cargo delivery. We prepared and characterized Janus Au–mesoporous silica nanoparticles functionalized with acetylcholinesterase on the Au face and with supramolecular β‐cyclodextrin:benzimidazole inclusion complexes as caps on the mesoporous silica face. The nanodevice is able to selectively deliver the cargo in the presence of acetylcholine via enzyme‐mediated acetylcholine hydrolysis, locally lowering the pH and opening the supramolecular gate. Given the key role played by ACh and its relation with Parkinson's disease and other nervous system diseases, we believe that these findings could help design new therapeutic strategies. Abstract : Janus Au–mesoporous silica nanoparticles functionalized with acetylcholinesterase on the Au face and with supramolecular β‐cyclodextrin:benzimidazole inclusion complexes as caps on the mesoporous silica face were made and characterized. The nanodevice is able to selectively deliver cargo in the presence of acetylcholine via enzyme‐mediated acetylcholine hydrolysis, locally lowering pH and opening the supramolecular gate.